Monetary Policy in an Inside-Money, Open Economy - Mathieson, Donald J. (Quarterly Journal of Economics, 1975)
Tobin's banking system model, 83. — Opening the Tobin model, 86. — Foreign sector, 86. — Stationary-state, portfolio balance, 87. — Banking sector, 89. — High-powered money, 89. — Aggregate demand and supply, 90. — Government sector, 91. — Monetary policy, 93. — Fixed exchange rate: increase in required reserve ratio, 94. — Floating exchange rate, 97. — Conclusions, 99. — Appendix I: notation, 100. — Appendix II, 100.